1995
DOI: 10.1002/pssa.2211510128
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the refractive index and absorption coefficient in the layer plane of gallium telluride single crystals

Abstract: Refractive index and absorption coefficient of GaTe for light polarized in the optical axis directions in the layer plane are determined from transmission measurements. The refractive index is determined in the wavelength range from 0.7 to 25 μm and the absorption coefficient in the range of energies from 1.6 to 2 eV at room temperature and at 30 K. The optical constants are found to be anisotropic in the layer plane. The refractive index dispersion is interpreted through a Phillips‐Van Vechten model and the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
2
36
1
2
Order By: Relevance
“…Although the structural, electrical, optical absorption and photoelectric properties have been widely investigated [6][7][8][9][10], only a few reports have been published on the metal/p-GaSe SBDs [11][12][13][14][15][16]. In contrast to other layered semiconductors [17][18][19][20][21], to my knowledge, measurements and modelling of the characteristic parameters for silver SBDs fabricated on p-GaSe have not yet 0925-8388/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structural, electrical, optical absorption and photoelectric properties have been widely investigated [6][7][8][9][10], only a few reports have been published on the metal/p-GaSe SBDs [11][12][13][14][15][16]. In contrast to other layered semiconductors [17][18][19][20][21], to my knowledge, measurements and modelling of the characteristic parameters for silver SBDs fabricated on p-GaSe have not yet 0925-8388/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to study the anisotropic structural and electronic transport properties of GaTe, 4,5 its refractive index, 6 and its physical properties under pressure. 7 Optical measurements have also been done: Camassel et al 8 performed absorption experiments at the liquid helium temperature and they found strong excitonic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Хорошо известно, что расчеты в рамках DFT приводят к заниженным значениям ширины запрещенной зоны E g полупроводников и изоляторов. Так, наши предыдущие расчеты для моноклинного m-GaTe в [3] дали E g около 0.94 eV, тогда как типичным результатом измерений спектров фотолюминесценции и оптического поглоще-ния для m-GaTe при комнатной температуре является E g = 1.65−1.66 eV [1,5]. С целью получения более близ-ких значений E g к результатам измерений оптической ширины запрещенной зоны, в настоящей работе исполь-зовалась систематическая поправка 0.72 eV к энергиям межзонных переходов нанослоев GaTe из расчетов в рамках DFT.…”
Section: результаты и обсуждениеunclassified
“…В отличие от слоистых сульфида и селенида галлия, имеющих гексагональную симметрию (наиболее общими полити-пами являются β-GaS и ε-GaSe с идентичными по своей структуре слоями), объемные кристаллы теллурида гал-лия кристаллизуются преимущественно в моноклинной сингонии (m-GaTe с пространственной группой B2/m). По своим электронным свойствам соединение m-GaTe является прямозонным полупроводником с шириной запрещенной зоны около 1.7 eV при комнатной темпе-ратуре [1]. Намеренно нелегированные образцы GaTe, а также GaSe и их твердые растворы как правило демонстрируют проводимость p-типа [2], что можно связать с положением уровня зарядовой нейтральности в нижней половине запрещенной щели [3,4].…”
Section: Introductionunclassified